Analisis Pengaruh Sertifikat Bank Indonesia Syariah (SBIS), Nilai Tukar (Kurs) Dan Inflasi Terhadap Pembiayaan Bermasalah Perbankan Syariah Di Indonesia Periode 2018-2021 - Sakinah Jahrani Nasution; Sri Sudiarti (Jurnal Ilmiah Ekonomi Islam, 2023)
This research aims to find out how to analyze the influence of Indonesian Islamic banks (SBIS), exchange rates (exchange rates) and inflation on problematic financing of Indonesian Islamic banking for the 2018-2021 period. The method used in this study is a mixed method. data collection for conducting this research are as follows: Field research, library research and internet research. In this study, researchers used quantitative analysis methods, namely the data used in this study were in the form of numbers. In this study using a quantitative method with a deductive format that starts from the general situation to the specific things. The result in this study show that Sertifikat Bank Indonesia Syariah (SBIS), Exchange Rate (Kurs) and Inflation have a significant effect on againts Non Performing Financing Islamic Bank. Sertifikat Bank Indonesia Syariah (SBIS) partially do not have a significant effect on Non Performing Financing. Exchange Rate (Kurs) and Inflation have a significant effect on Non Performing Financing.